Metode Pembelajaran Dalam Kisah Nabi Adam dan Relevansinya di Masa Sekarang (Kajian Q.S Al-Baqarah Ayat 31-34) - Cahya Satria Prayoga Bakti; Ngarifin Shidiq; Muhammad Saefullah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The meaningful learning story of Prophet Adam in Q.S Al-Baqarah Ayat 31-34 describes the educational interaction between Allah SWT, the Angels, and Prophet Adam AS. This story is full of meaning about the learning process. The Learning Methods in the story of Prophet Adam include the Story Method, Direct Instruction, Questioning Method, and Demonstration Method. These methods are very effective and relevant to modern education. These methods can be combined to create learning that is interesting, effective, and relevant to the needs of today's students. Teachers can utilize various media and technology to support the implementation of these methods. The right and effective methods will produce an intelligent, humanist, and noble generation. This research focuses on the learning methods in the story of Prophet Adam in Q.S. Al-Baqarah Ayat 31-34. By studying the learning methods in the story of Prophet Adam, educators can find new inspiration and insights to design effective learning methods in the modern era.